Fisher’s and Modified Millard-Onizuka Techniques for Unilateral Cleft Lip Repair: Comparison of Surgical Outcomes and Patient Satisfaction - Kristaninta Bangun; Andi Azwadi Rais; Vika Tania; Puri Ambar Lestari; Dhita Kurniasari; Vania Aramita Sari; Clara Menna (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2026)
Introduction: Unilateral cleft lip (UCL) surgery aims to achieve symmetry and correct functional and aesthetic issues. The Millard technique dominated until 2005, when Fisher introduced a new surgical method that is still in use today. This study aims to compare the symmetry outcomes and patient satisfaction levels between the Fisher and Modified Millard-Onizuka techniques.Method : A retrospective cohort study was conducted to compare the outcomes of the Fisher and Modified Millard-Onizuka techniques in patients with UCL who had undergone cleft lip surgery. Five experienced plastic surgeons assessed photographs using Steffensen’s criteria, while patients and parents completed the Cleft Evaluation Profile satisfaction questionnaire. Data were analysed using SPSS v.29.Results: The intraclass correlation test showed a Cronbach’s alpha >0.7 for all criteria, indicating strong reliability. Statistical analysis revealed no significant differences in Steffensen's criteria scores among the five raters between the study groups. However, the satisfaction questionnaire indicated higher satisfaction with dental appearance in the Fisher technique group. This finding may be attributed to the fact that all patients in this group were treated at a multidisciplinary cleft centre.Conclusion: Surgical outcomes and patient satisfaction after cleft lip surgery using Fisher’s technique are comparable to the modified Millard-Onizuka technique.